Analysis of Porosity and Undercut Defects in Structural Steel Grade S355JR Fabrication - Sadrak Jhoshua Nababan; Hery Irwan (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
This study aimed to identify the dominant causes of porosity and undercut defects and evaluate the effectiveness of welding defect control measures applied during the fabrication of S355JR Structural Steel in an E-house project at PT.X Batam. A descriptive qualitative approach supported by quantitative data was employed through field observations, semi-structured interviews, documentation, and Pareto and fishbone analyses. The results indicated that welding defects were predominantly caused by welding method (10 joints; 34.5%), followed by environmental factors (7 joints; 24.1%), machine conditions (5 joints; 17.2%), material conditions (4 joints; 13.8%), and welder skill (3 joints; 10.3%). The findings showed that improper welding parameters, unstable shielding gas due to wind exposure, inadequate equipment condition, contaminated material surfaces, and inconsistent implementation of the Welding Procedure Specification (WPS) were the principal contributors to defect occurrence. Corrective measures, including material surface cleaning, dry electrode usage, rod oven storage, welding parameter control, and welding habitat protection, effectively reduced the occurrence of porosity and undercut defects. The novelty of this study lies in the integrated evaluation of technical and operational factors affecting welding quality under actual EPC fabrication conditions. The findings provide practical guidance for improving welding quality control and reducing production losses in structural steel fabrication.